2023
DOI: 10.3389/fmed.2023.1145889
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of learning outcomes of humanities curricula in medical students. A meta-review of narrative and systematic reviews

Abstract: ObjectivesTo assess the expected learning outcomes of medical humanities subjects in medical studies curricula. To connect those expected learning outcomes with the types of knowledge to be acquired in medical education.MethodsMeta-review of systematic and narrative reviews. Cochrane Library, MEDLINE (Pubmed), Embase, CINAHL, and ERIC were searched. In addition, references from all the included studies were revised, and the ISI Web of Science and DARE were searched.ResultsA total of 364 articles were identifie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 32 publications
0
3
0
Order By: Relevance
“…Nevertheless, they stated that these studies contribute to the "discursive construction of humanities as a necessary component of medical education" [42] (p. 992). A recent meta-review on the evaluation of learning outcomes in humanities curricula [43] identified four clusters of learning outcomes: (1) adequate communication; (2) development of skills to help in problem solving, reflexive competence, personal well-being, handling burnout, coping with uncertainty and end-of-life care, and developing critical and creative thinking; (3) ethical compliance; and (4) teamwork. This review did not mention GnCs as a method of medical humanities, probably because, at present, there are no robust studies on the evaluation of the effect of GnCs.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, they stated that these studies contribute to the "discursive construction of humanities as a necessary component of medical education" [42] (p. 992). A recent meta-review on the evaluation of learning outcomes in humanities curricula [43] identified four clusters of learning outcomes: (1) adequate communication; (2) development of skills to help in problem solving, reflexive competence, personal well-being, handling burnout, coping with uncertainty and end-of-life care, and developing critical and creative thinking; (3) ethical compliance; and (4) teamwork. This review did not mention GnCs as a method of medical humanities, probably because, at present, there are no robust studies on the evaluation of the effect of GnCs.…”
Section: Discussionmentioning
confidence: 99%
“…Students who have exposure to humanities subjects are more likely to become empathetic clinicians [40], they also tend to have better tolerance and emotional resilience [41]. To cultivate medical professionals with compassion, love, and warmth, medical humanities education is essential, common medical humanities courses include history, ethics, narrative medicine, literature, and art [42] [43].…”
Section: Humanistic Accomplishmentmentioning
confidence: 99%
“…The study of humanities subjects is part of the necessary knowledge for good clinical practice [42]. However, medical education in China is still dominated by natural sciences, with only 7.54% of the curriculum dedicated to humanities, much lower than in European and American countries (20% -26%).…”
Section: Humanistic Accomplishmentmentioning
confidence: 99%